Diagnosis and Treatment of Hypospadias With Megameatus Intact Prepuce - Duan, Shou Xing; Li, Jianhong; Jiang, Xuewu; Zhang, Xuan; Ou, Wenhui; Fu, Maxian; Chen, Kaihong; Zheng, Lian; Ma, Shu Hua (Frontiers in Pediatrics, 2020)
Purpose: To evaluate the recognition and treatment methods of hypospadias with megameatus intact prepuce (MIP). Materials and Methods: A retrospective analysis was performed in 27 MIP children, 13 of whom underwent tubularized incised plate urethroplasty (TIP procedure), 7 underwent the Duplay procedure, 5 underwent the Mathieu procedure, 1 underwent meatal advancement and glanuloplasty (MAGPI procedure), and 1 underwent the glans approximation procedure (GAP). The five patients were followed for 6 to 36 months to evaluate the surgical outcomes. Results: A total of 27 patients with a mean age of 8.12±3.0 years were enrolled in this study, and 25 cases (25/27, 92.6%) were accidentally discovered during the first visit for phimosis. The patients had a formed urethra of 0.5 to 1.5 cm. Complications occurred in 4 of the 27 patients (14.81%): 2 patients with urethral fistula and 2 patients with meatal stenosis. One patient had a case of self-healed urethral fistula, and the remaining 3 patients underwent reoperation. The appearance of the penis postsurgery was satisfactory in all patients, and the urinary flow and stream during urination were normal. Conclusions: MIP clinical manifestations are concealed and usually noted when circumcision is attempted. The suitable procedure for each patient should be tailored according to the anatomic features, and several techniques can be used with good functional and cosmetic results.